Peranan Sistem dan Teknologi Pada Proses Bisnis Organisasi - Idris, Muhammad; Nasution, Muhammad Irwan Padli (Universitas Muhammadiyah Enrekang, 2024)
Information technology is needed in the organization and operation of business enterprises. Utilization of information technology in a function of the organization is divided into five elements, namely functions: 1). Operational functions, 2). Monitoring and Control function, 3). Planning and Decision Function, 4). Communication functions, and 5). Interorganisational function. The whole role of information technology in the various layers may not function properly without the governance and management of information technology is good, because basically the goal is to use information technology to achieve the goals of the organization or company. Technology in organizations have a major role in studying the properties of an organization's technology and technology relationship to organizational structure. Thomson grouping technology organizations into three types: 1) Mediating Technology, 2) Long-linked Technology, 3) Intensive Technology.